Effect of Emotional Intelligence and Personality Traits on the Psychological Well-Being of University Students in Malaysia - Kassandra Aiman Rahmat Effandi; Muhammad Idris Bullare@Bahari; Hajah Siti Rafidah Haji Md Said (Society for Research and Knowledge Management Ltd, 2023)
Psychological distress has been an increasing issue among university students, mainly due to the changes that have taken place brought about by the COVID-19 pandemic. It was found that there needs to be more evidence surrounding the topic of psychological well-being (PWB) among university students in Malaysia. This study has examined the effect of emotional intelligence (EQ) and personality traits on the PWB of university students in Malaysia. A quantitative research method using convenience sampling was used in this study. One hundred fifty-one (151) students from public and private universities in Malaysia participated in the study. The questionnaires were used as data-collecting tools and were distributed in Google Forms. Data were analysed using IBM SPSS version 28.0. Regression analysis showed no significant effect of EQ on the PWB of the students. In disparity, personality traits significantly influenced both PWB and EQ of university students in Malaysia. The findings of this study highlight that certain personality traits contribute considerably to the PWB of university students in Malaysia. Hence, it is suggested that university administrators, university students, and other researchers investigate the role of these personality traits in enhancing PWB and EQ among university students.